2006
DOI: 10.2134/agronj2005-0131
|View full text |Cite
|
Sign up to set email alerts
|

Boron Fertilization Influences on Soybean Yield and Leaf and Seed Boron Concentrations

Abstract: Soybean [Glycine max (Merr.) L.] is considered relatively insensitive to B deficiency. However, B deficiency has recently become a common nutrient deficiency of soybean in northeast Arkansas. Field studies were conducted on four alkaline silt‐loam soils in northeast Arkansas to determine the influence of B application time and rate on soybean growth, tissue B concentration, and seed yield. Boron fertilizer was applied at 0, 0.28, 0.56, 1.12, and 2.24 kg B ha−1 near the V2 or R2 growth stages. Boron fertilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 18 publications
5
40
3
1
Order By: Relevance
“…The positive effect of B on different crops was also previously reported by many researchers, i.e. on tomato (Salam et al, 2009), wheat (Güneş et al, 2003), sunflower (Oyinlola, 2007), pepper and cucumber , celery (Dambrauskienè et al, 2007), and soybean (Ross et al, 2006). As a result of these investigations, it was reported that different B applications increased the nutrient content, plant growth, and yield of different plant species.…”
Section: Growth and Yield Parameterssupporting
confidence: 73%
“…The positive effect of B on different crops was also previously reported by many researchers, i.e. on tomato (Salam et al, 2009), wheat (Güneş et al, 2003), sunflower (Oyinlola, 2007), pepper and cucumber , celery (Dambrauskienè et al, 2007), and soybean (Ross et al, 2006). As a result of these investigations, it was reported that different B applications increased the nutrient content, plant growth, and yield of different plant species.…”
Section: Growth and Yield Parameterssupporting
confidence: 73%
“…Boron application at the rate of 1.0 kg ha -1 increased effective pod per plant while boron at the rate of 2.0 kg B ha -1 produced higher 100 seed weight significantly. Similarly, Ross et al, (2006) found that there was increase in the number of plant nodes and plant height in soybean crop with increasing levels of boron up to 1.12 kg B ha -1 , however, significant increase was observed up to 0.56 kg B ha -1 of application. Hemantaranjan et al, (2000) observed that foliar application of boron as boric acid at the rate of 50 mg kg -1 and 100 mg kg -1 boron on soybean increased morpho-physiological attributes, total dry matter production and seed yield.…”
Section: Responses Of Oilseed Crops To Boron Applicationmentioning
confidence: 79%
“…In our study, leaf tissue B content at the OEBR was similar to the B content of grapevine. Several scientists, such as Guertal (2004), Santos et al (2004), and Ross et al (2006) suggested that 10 mg/kg, 66 mg/kg, and 44.1 mg/kg in some plant tissues is the critical level for B in bentgrass, alfalfa, and soybean, respectively. Mills and Jones (1996) suggested critical leaf and berry values for optimum grapevine growing as follows: 1.6%-2.8%, 2.0%-2.6% for N; 0.2%-0.6%, 0.3%-0.5% for P; 1.5%-5.0%, 0.8%-2.2% for K; 0.4%-2.5%, 1.5%-5.5%, for Ca; 0.13%-0.4%, 0.2%-1.0% for Mg; 35-200 mg/kg, 60-200 mg/kg for Fe; 10-100 mg/kg, 25-150 mg/kg for Zn; 40-600 mg/kg, 25-200 mg/kg for Mn; and 4-20 mg/ kg, 5-20 mg/kg for Cu.…”
Section: Discussionmentioning
confidence: 99%